Effect of Matrica Mouth Wash on Prevention of Head and Neck Radiotherapy Induced-Stomatitis - Shiva Sadat Bassampour; Fatemeh Bahramnezhad; Eisa Mohammadi; Mohammad Hassan Larizadeh; Shadan Pedram Razi; Hamid Haghani (Tehran University of Medical Sciences, 2012)
Background & Aim: Oral care and using mouthwash help to prevent stomatitis. The aim of this study was to investigate the effect of two mouth wash protocols on prevention of head and neck radiotherapy induced-stomatitis. Methods & Materials: In this single blind clinical trial, 120 individual were recruited. The experiment group (N=40) gurgled with 3cc of Matrices mouthwash and the control group used water mouth wash. The participants were assessed using the WHO grading scale. Data were analyzed using the Fisher exact test and Mann-Whitney U test as appropriate. Results: There was not significant differences between the experimental and control groups regarding stomatitis intensity in the first day (P=0.371). Tere were significant differences between the two groups regarding stomatitis intensity in days 7 and 14 (P<0.001). Conclusion: Oral stomatitis is a common condition in patients with head and neck radiotherapy. It makes painful ulcers, dehydration, malnutrition, and potentially life-threatening infection. Matrica mouth wash could prevent and treat induced-radiotherapy ulcer stomatitis.